2022
DOI: 10.1155/2022/2697303
|View full text |Cite
|
Sign up to set email alerts
|

A Machine Learning-Based Model for Stability Prediction of Decentralized Power Grid Linked with Renewable Energy Resources

Abstract: A decentralized power grid is a modern system that implements demand response without requiring major infrastructure changes. In decentralization, the consumers regulate their electricity demand autonomously based on the grid frequency. With cheap equipment (i.e., smart meters), the grid frequency can be easily measured anywhere. Electrical grids need to be stable to balance electricity supply and demand to ensure economically and dynamically viable grid operation. The volumes of electricity consumed/produced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…We evaluate our model by comparing it with other machine-learning models. The results are compared in terms of accuracy, precision, recall, and F1-Score, which can be calculated using parameters which are defined as [ 59 , 60 , 61 , 62 ]: True Positive (TP): It identifies how much the data instances are identified as recovery cases. True Negative (TN): It identifies how many data instances are categorised as death cases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We evaluate our model by comparing it with other machine-learning models. The results are compared in terms of accuracy, precision, recall, and F1-Score, which can be calculated using parameters which are defined as [ 59 , 60 , 61 , 62 ]: True Positive (TP): It identifies how much the data instances are identified as recovery cases. True Negative (TN): It identifies how many data instances are categorised as death cases.…”
Section: Resultsmentioning
confidence: 99%
“…The most prevalent sign of advanced hepatic illness is ascites. The ascitic subtype of advanced Schistosomiasis is the most dangerous, accounting for 65–90 percent of cases [ 60 ]. Granulomatous inflammation can be caused by venous blockage and portal hypertension and leads to continuous fibrosis and a drop in plasma colloid osmotic pressure [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…The information may be used to build models for predicting academic success, locating at-risk students, and spotting problematic behavior. It is designed for use in research on student behavior and performance [38][39][40][41][42][43][44][45][46][47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…The study found the key areas of crucial local characteristics work in conjunction with the attention mechanism to exploit each expert’s job from many aspects fully. Seventy-five percent accuracy was achieved [ 20 ].…”
Section: Literature Reviewmentioning
confidence: 99%